Analysis of Customer Behavior in Mobile Food Ordering Application Using UTAUT Model (Case Study: GoFood Application) - F., Viqha; Izzati, Berlian Maulidya (School of Industrial and System Engineering, Telkom University, 2020)
One of the mobile application technologies that popular and enjoying extraordinary success in Indonesia is GoJek application. One of many services in gojek app is called go-food. Go-food provides food online service delivery that has three main users. There are merchants, gojek drivers, and customers. Many online food ordering applications have developed, and various issues have occurred, but there has not been much research on the topic. This research is using quantitative methods. Tools to get data is a questionnaire of 60 respondents. The results are validation data and structural model calculation use Smart PLS tools. From the measurement results, there are two variables that have a positive and significant effect (with a t-statistic score> 1.65) on the user's intention to use GoFood, namely the Social Influence and Perceived Control variables. There also performance expectancy, effort expectancy, and facilitating condition variables that have a negative effect (with a t-statistic score <1.65) on the user's intention to use the GoFood application.